2014
DOI: 10.1371/journal.pcbi.1003478
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design of the Affinity and Specificity of a Therapeutic T Cell Receptor

Abstract: T cell receptors (TCRs) are key to antigen-specific immunity and are increasingly being explored as therapeutics, most visibly in cancer immunotherapy. As TCRs typically possess only low-to-moderate affinity for their peptide/MHC (pMHC) ligands, there is a recognized need to develop affinity-enhanced TCR variants. Previous in vitro engineering efforts have yielded remarkable improvements in TCR affinity, yet concerns exist about the maintenance of peptide specificity and the biological impacts of ultra-high af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
101
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 60 publications
6
101
0
Order By: Relevance
“…For analysis of D26α-Arg65 pair, the L98βW single mutant was used. We note that, excluding the sites of the two mutations, the structures of the high-affinity and wild-type DMF5 TCR complexes are essentially identical (13,65). The utilization of affinity-enhancing mutations is unlikely to impact the double-mutant cycle experiments, owing to the structural similarities and the robust nature of double-mutant cycle analysis (40,41).…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…For analysis of D26α-Arg65 pair, the L98βW single mutant was used. We note that, excluding the sites of the two mutations, the structures of the high-affinity and wild-type DMF5 TCR complexes are essentially identical (13,65). The utilization of affinity-enhancing mutations is unlikely to impact the double-mutant cycle experiments, owing to the structural similarities and the robust nature of double-mutant cycle analysis (40,41).…”
Section: Methodsmentioning
confidence: 92%
“…Errors were propagated using standard statistical error propagation methods (63). High-affinity variants of the DMF5 TCR were used to facilitate the analysis (65). For analysis of Tyr48β-Arg65 pair, the D26αY/L98βW double mutant was used.…”
Section: Methodsmentioning
confidence: 99%
“…The A6 and B7 TCRs also share the same germlinederived Vβ chain, although crystallographic structures and biophysical studies of A6 and B7 with Tax 11-19 /HLA-A2 showed structural and thermodynamic differences in binding (Davis-Harrison et al, 2005). We modeled 740 point mutations in the B7-Tax 11-19 /HLA-A2 interface using Rosetta (Das and Baker, 2008;Kaufmann et al, 2010) and the scheme described in Pierce et al (2014). As performed previously, effects were determined by scoring the complex, then separating the components and separately scoring the TCR and pMHC in order to calculate a 'binding score' (Kortemme and Baker, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…1b). Utilizing the ZAFFI score function first developed for the A6 TCR and refined with the DMF5 TCR (Haidar et al, 2009;Pierce et al, 2014) led to an improved but still weak correlation (R = 0.47; Fig. 1c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation